2005
DOI: 10.1110/ps.051442305
|View full text |Cite
|
Sign up to set email alerts
|

Rv0216, a conserved hypothetical protein from Mycobacterium tuberculosis that is essential for bacterial survival during infection, has a double hotdog fold

Abstract: The Mycobacterium tuberculosis genome contains about 4000 genes, of which approximately a third code for proteins of unknown function or are classified as conserved hypothetical proteins. We have determined the three-dimensional structure of one of these, the rv0216 gene product, which has been shown to be essential for M. tuberculosis growth in vivo. The structure exhibits the greatest similarity to bacterial and eukaryotic hydratases that catalyse the R-specific hydration of 2-enoyl coenzyme A. However, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…Rv0098 is thought to be one of only 219 essential core genes in mycobacteria (33). As an aside, Rv0216, whose gene product was also tested here for complementation, is also a core gene (11). Furthermore, Rv0098 is required for the survival of M. tuberculosis in mouse lung macrophages (40), and has homologues in M. leprae, M. bovis, and M. smegmatis (41).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Rv0098 is thought to be one of only 219 essential core genes in mycobacteria (33). As an aside, Rv0216, whose gene product was also tested here for complementation, is also a core gene (11). Furthermore, Rv0098 is required for the survival of M. tuberculosis in mouse lung macrophages (40), and has homologues in M. leprae, M. bovis, and M. smegmatis (41).…”
Section: Discussionmentioning
confidence: 98%
“…The strains used were yPLM35 and yPLM43. (11,41). Of these, Rv0130, denoted HtdZ (21), and Rv0635-Rv0636 and Rv0636-Rv0637, referred to as HadAB and HadBC (9, 37), have since been identified as physiological dehydratases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, M. tuberculosis FAS-II has proven as a clinically relevant target (Banerjee et al, 1994;Dover et al, 2007;Kremer et al, 2000). Previous analyses by Castell et al (2005) first suggested that Rv0636 of M. tuberculosis H37Rv is a good candidate for the unidentified b-hydroxyacyl-ACP dehydratase of FAS-II. The gene encoding Rv0636 is not only predicted to be essential (Sassetti et al, 2003), but is highly conserved over numerous mycobacterial species such as M. bovis, M. smegmatis and importantly M. leprae.…”
mentioning
confidence: 99%